2018
DOI: 10.1128/mcb.00195-17
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-Binding Protein CG5445 Suppresses Aggregation and Cytotoxicity of Amyotrophic Lateral Sclerosis-Linked TDP-43 in Drosophila

Abstract: Ubiquitin-mediated protein degradation plays essential roles in proteostasis and is involved in the pathogenesis of neurodegenerative diseases in which ubiquitin-positive aberrant proteins accumulate. However, how such aberrant proteins are processed inside cells has not been fully explored. Here, we show that the product of , a previously uncharacterized gene, prevents the accumulation of aggregate-prone ubiquitinated proteins. We found that ubiquitin conjugates were associated with CG5445, the knockdown of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…4A and B ). A number of proteins have been reported to play a role in TDP43 clearance ( 65 , 78 80 ). Recently, the β4-strand of the RRM2 domain of human TDP43 was shown to harbor a degradation signal recognized by the VHL/ElonginB/C/Cul2/Rbx1 complex ( 80 ).…”
Section: Discussionmentioning
confidence: 99%
“…4A and B ). A number of proteins have been reported to play a role in TDP43 clearance ( 65 , 78 80 ). Recently, the β4-strand of the RRM2 domain of human TDP43 was shown to harbor a degradation signal recognized by the VHL/ElonginB/C/Cul2/Rbx1 complex ( 80 ).…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies. The antibodies against Rpn1 to -3, Rpn6 to -8, Rpn10, Rpn13, Rpt1 to -6, ␣2, ␤3, Uch37, Usp14, Txnl1, HHR23b, and PA28␥ were described previously (62)(63)(64)(65)(66)(67). Polyclonal antibodies against Rpn5, Rpn9, Rpn11, EGFP, and HaloTag were raised in rabbits by using recombinant proteins of human Rpn5 (residues 1 to 161), human Rpn9 (full length), human Rpn11 (residues 171 to 287), EGFP (full length), and HaloTag (full length), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…This indicates that the level of TDP-43 must be tightly regulated throughout life. GOF experiments also revealed that excess of TBPH or TDP-43 is highly toxic in muscles [ 270 , 306 , 307 ], glial cells [ 270 , 307 , 309 , 325 , 326 ], and in the eye [ 266 , 274 , 289 , 290 , 292 , 293 , 302 , 303 , 304 , 306 , 307 , 310 , 312 , 314 , 315 , 316 , 317 , 318 , 319 , 320 , 324 , 327 , 328 , 329 , 330 , 331 , 332 , 333 , 334 ]. Moreover, it was reported that TBPH or TDP-43 overexpression induces cell death, as was shown in motoneurons [ 266 , 289 , 290 , 301 ], glial cells [ 309 , 326 ], mushroom bodies [ 265 , 290 ], and in the eye.…”
Section: Tdp-43 Proteinopathy In the Fruit Flymentioning
confidence: 99%
“…This may explain some discrepancies between different GOF studies ( Table 9 and Table 10 ). Several phenotypes induced by TBPH /TDP-43 GOF, such as eye degeneration and climbing defects, show age-dependent progression [ 265 , 275 , 289 , 290 , 293 , 305 , 307 , 308 , 309 , 311 , 312 , 314 , 315 , 316 , 318 , 320 , 321 , 324 , 325 , 330 , 331 , 332 , 333 , 334 ]. As TBPH expression decreased with aging [ 338 ], one may speculate that reduced endogenous TBPH levels exacerbate GOF effects without excluding that phenotype aggravation may be due to continuous abnormal accumulation of TBPH /TDP-43.…”
Section: Tdp-43 Proteinopathy In the Fruit Flymentioning
confidence: 99%
See 1 more Smart Citation